Effect of lamotrigine on epilepsy‐induced cognitive impairment and hippocampal neuronal apoptosis in pentylenetetrazole‐kindled animal model. Issue 2 (1st December 2016) - Zhang, Bing; Zhang, Jia‐Wei; Wang, Wei‐Ping; Dong, Rui‐Fang; Tian, Shuang; Zhang, Chao
Abstract: Purpose: Lamotrigine (LTG) is a broad‐spectrum antiepileptic drug that is widely used in clinic. However, the effect of LTG on cognition and neurodegeneration during epilepsy treatment remains controversial. In this study, we compared the cognitive effects of LTG and sodium valproate in pentylenetetrazole (PTZ)‐kindled animal model, and the dose dependency was tested for LTG. Methods: PTZ‐kindled animals were divided into the following treatment groups: control group, treated with 3.5 mL/kg of 0.9% sodium chloride; low‐dose LTG group, treated with 12.5 mg/kg of LTG; middle‐dose LTG group, treated with 25 mg/kg of LTG; high‐dose LTG group, treated with 50 mg/kg of LTG; VPA group, treated with 300 mg/kg of VPA. The Morris Water Maze (MWM) test commenced from the 10th day of treatment. Hippocampal cell apoptosis was determined by TUNEL staining after two weeks of treatment. Results: Compared to the vehicle‐treated control group, escape latency was significantly reduced in the middle‐ and high‐dose LTG‐ and VPA‐treated groups on the 3rd and 4th day of the MWM test ( p  < .05), and spatial probe frequency was significantly improved in the middle‐ and high‐dose LTG‐ and VPA‐treated groups ( p  < .05). Furthermore, the immunohistochemical score of TUNEL positive cells significantly decreased in the hippocampal CA1 region in the middle‐ and high‐dose LTG‐ and VPA‐treated groups ( p  < .05). Conclusion: Our data suggests that LTG may ameliorate epilepsy‐induced cognitive impairment and neuronal cell apoptosis during epilepsy treatment. LTG may ameliorate cognitive impairment and neuronal cell apoptosis during epilepsy treatment. Abstract : LTG may ameliorate cognitive impairment and neuronal cell apoptosis during epilepsy treatment.